Local Climatological Data Summary: Decatur, Illinois, 1901-1990 - Bryan, Audrey A.; Armstrong, Wayne (Illinois State Water Survey, 1991)
Decatur (Macon County) has a temperate continental climate, dominated by maritime tropical air from the Gulf of Mexico from about late April through mid-October. Gulf air generally supports relative humidities of about 50% during the day and 85% at night. During these months, there are occasional, brief interruptions of drier, cooler air from the Pacific Ocean, but typically only last for a few days. During the remainder of the year, the Decatur area is dominated by Pacific Ocean air. Four to six times each winter, cold, dry air from the Canadian Arctic breaks south, bringing temperatures into the units or values even less than zero. is peer reviewed Submitted by Agnes Stankiewicz (stankie2@illinois.edu) on 2014-10-29T15:28:26Z No. of bitstreams: 1 ISWSMP-98-3.pdf: 426489 bytes, checksum: 9573ad36c71576b4edcac67b6ef77c34 (MD5) Made available in DSpace on 2014-10-29T15:28:26Z (GMT). No. of bitstreams: 1 ISWSMP-98-3.pdf: 426489 bytes, checksum: 9573ad36c71576b4edcac67b6ef77c34 (MD5) Previous issue date: 1991 published or submitted for publication Open